(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Physical properties of reservoir fluid are necessary for different field applications. Among those properties is the Oil Formation Volume Factor (Bo). It is one of important property for both reservoir and production engineering. In many situations, laboratory measurement is not possible either because of unavailability of liquid oil samples or budget constraints, Hence, proper empirical correlations to predict formation volume factor come to rescue. The purpose of this exploration is to test the performance of the most common published Oil Formation Volume Factor correlations for selected Libyan crude oils. Statistical analysis is the criteria adopted for the evaluation in this study. Cross plot technique is also applied to check the performance of the correlation and it gave the same index of the statistical criteria method. Accuracy of these correlations has been confirmed by comparing the obtained results of these correlations with experimental data gathered from our labs for Libyan oil reservoirs. It was observed that, there is acceptable agreement between predicted results with experimental results.